2011
DOI: 10.1111/j.1471-0528.2011.03030.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring age differences in reasons for nonattendance for cervical screening: a qualitative study

Abstract: Objectives To explore differences in barriers to attendance at cervical screening across age groups because coverage of the cervical screening programme in England has been falling, particularly among women in the youngest age group (25-29 years).Design A qualitative study.Setting A university in London.Sample Professionals working in the screening field (n = 12) and women of varying ages who had either never attended for cervical screening or did not attend regularly (n = 46). MethodsIn Study 1 we interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 21 publications
9
103
2
3
Order By: Relevance
“…Practical obstacles dominated, as seen in other studies, [30][31][32] especially among young women. 33 The most common special request was for a convenient appointment and more than half actually booked outside the regular screening schedule. This may be a manifestation of poor accessibility in the regular screening program and scheduling of appointments can no doubt be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Practical obstacles dominated, as seen in other studies, [30][31][32] especially among young women. 33 The most common special request was for a convenient appointment and more than half actually booked outside the regular screening schedule. This may be a manifestation of poor accessibility in the regular screening program and scheduling of appointments can no doubt be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Embarrassment and perceived indignity are often cited by older women as important barriers to screening (Armstrong, 2007;Van Til et al, 2003;Waller, Bartoszek, Marlow & Wardle, 2009;Waller, Jackowska, Marlow & Wardle, 2012;White, 1995). Embarrassment when requesting an appointment and anxiety prior to screening can be severe (Van Til et al, 2003;Armstrong, 2007).…”
Section: Embarrassmentmentioning
confidence: 99%
“…However, Waller et al, (2012) conducted a qualitative study with British women and found that older women were more concerned with emotional barriers such as embarrassment or fear rather than logistical issues compared to their younger counterparts. Logistical barriers may be more resonant among younger women for example due to moving address more often .…”
Section: Logistical Barriersmentioning
confidence: 99%
“…Some women, particularly those who have experienced abuse 14 or are otherwise marginalized, may find self-sampling preferable because of such things as cultural/religious embarrassment or discomfort associated with a pelvic exam 13,[15][16][17] . Time, transportation, inconvenient clinic hours, or not having a regular practitioner are also relevant factors associated with under-screening that can be mitigated through hpv self-collection using mailed samples 13,16,17 . However, there are psychosocial barriers to hpv screening, including women's lack of awareness and fears around hpv and cervical cancer screening, which cannot be addressed through self-collection-based screening alone 17,18 .…”
Section: Paradigm Shift Towards Hpv Screening Globallymentioning
confidence: 99%